To solve the equation \( 5(x+3) − 7(x−4) = 38 \), you can follow these steps:
-
Distribute the Terms: Apply the distributive property to eliminate the parentheses.
- \( 5(x + 3) = 5x + 15 \)
- \( -7(x - 4) = -7x + 28 \)
-
Rewrite the Equation: Substitute the distributed terms back into the equation.
- \( 5x + 15 - 7x + 28 = 38 \)
-
Combine Like Terms: Combine the terms on the left side of the equation.
- \( (5x - 7x) + (15 + 28) = 38 \)
- This simplifies to \( -2x + 43 = 38 \)
-
Isolate the Variable: Move constant terms to the right side by subtracting 43 from both sides.
- \( -2x = 38 - 43 \)
- \( -2x = -5 \)
-
Solve for \( x \): Divide both sides by -2 to find \( x \).
- \( x = \frac{-5}{-2} \)
- \( x = \frac{5}{2} \) or \( 2.5 \)
-
Check the Solution: Substitute \( x = \frac{5}{2} \) back into the original equation to verify it.
- Calculate \( 5\left(\frac{5}{2} + 3\right) - 7\left(\frac{5}{2} - 4\right) \)
- \( = 5\left(\frac{5}{2} + \frac{6}{2}\right) - 7\left(\frac{5}{2} - \frac{8}{2}\right) \)
- \( = 5\left(\frac{11}{2}\right) - 7\left(\frac{-3}{2}\right) \)
- \( = \frac{55}{2} + \frac{21}{2} \)
- \( = \frac{76}{2} = 38 \)
The left side equals the right side, confirming that the solution is correct.
Final Solution: \( x = \frac{5}{2} \) or \( x = 2.5 \)